Negociando a narrativa da madrasta: novas perspectivas para a vilã dos contos de fadas - Oliveira, Lívia Maria de (2021)
Fairy tales are configured as magical constructions of the world that permeate the centuries. In contemporary times, there is an intertextual movement to re-read these narratives that retakes the past under the concept of “re-vision”, proposed by Adrienne Rich (1985), betting on the need to deconstruct, reorganize and transform fairy tales, based on tradition. In this sense, contemporary revisionism, dialoguing with postmodernity, sheds light on perspectives that are outside the homogenizing system, demonstrating that these stories do not need to be as they always were and their meanings do not need to be unique, immutable or crystallized. As metaphors of an era, for a long time, these narratives established places for female characters. With the institutionalization of fairy tales as a literary genre, the stepmother started to occupy the negative feminine pole, being the counterpoint that validates the maternal ideal of kindness and fighting, within a new marriage, against her stepdaughter. Stepmother and stepdaughter are characters that build a relationship of power, being mutual influences for the development of the narrative. But why is the stepmother vilified and why does she have only the antagonist role in tradition? These initial questions led us to the development of this thesis, which tries to negotiate the narrative of the stepmother, based on reinterpretations of the traditional tale of Snow White. Reflecting the contemporary need to bring explanations about the stepmother's past in order to justify her villainy, we analyzed “The Snow Child”, by Angela Carter, “Snow Night”, by Barbara G. Walker, “The dead Queen”, by Robert Coover, Girls made of Snow and Glass, by Melissa Bashardoust, Fairest of All: A Tale of the Wicked Queen, by Serena Valentino; and Once upon a time, by Adam Horowitz and Edward Kitsis. Through these narratives, we defend the hypothesis that the search for the origin of the stepmother's evil is a fiction that does not impoverish the enigma, that is born and is consolidated in the fact of never saying everything, and we elaborated the concept of “origin-memory”, associating it with the transformation of the villainous stepmother into a postmodern anti-heroine.